Sources of Forecast Errors for Rainstorms in the South China Monsoon Region - Lin Lin; Chuhan Lu; Feifan Zhou (Advances in Meteorology)
The possible sources of forecast errors associated with rainstorms in the South China monsoon region were investigated based on Weather Research and Forecasting (WRF) model forecasts for 19 rainstorm cases that occurred in the past 13 years. Two datasets were separately selected as the initial fields of WRF with the same physical parameterization schemes. By investigating the improvement rate of the forecast when using one set of data rather than the other, the important degree of the initial conditions with respect to the forecasts for each case has been obtained. For those initial errors are the important sources of forecast errors, we further explored the source of the initial errors by comparing the two initial conditions. It was found that, interestingly, the significant differences between two initial conditions are all located upstream the rainfall area, with a distance of 5° of longitude away and an area of about 4° × 4°. Based on this, we developed a new method (which we refer to as the “guide flow method”) to identify the sensitive area for rainstorm forecasts in the South China monsoon region and then examined the efficiency of the sensitive areas. It was found that reducing the initial errors in the sensitive areas leads to better forecast results than doing the same in other areas. Thus, the sensitive areas are the source areas of forecast errors for rainstorms in the South China monsoon region.